2019
DOI: 10.15252/emmm.201809081
|View full text |Cite
|
Sign up to set email alerts
|

Stromal fibroblast growth factor 2 reduces the efficacy of bromodomain inhibitors in uveal melanoma

Abstract: Alterations in transcriptional programs promote tumor development and progression and are targetable by bromodomain and extraterminal (BET) protein inhibitors. However, in a multi‐site clinical trial testing the novel BET inhibitor, PLX51107, in solid cancer patients, liver metastases of uveal melanoma (UM) patients progressed rapidly following treatment. Mechanisms of resistance to BET inhibitors in UM are unknown. We show that fibroblast growth factor 2 (FGF2) rescued UM cells from growth inhibition by BET i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 49 publications
3
54
0
Order By: Relevance
“…The combination of the fibroblast growth factor receptor (FGFR) inhibitor AZD4547 with PLX51107 inhibited the growth of UM cells co-implanted with human stellate cells, indicating that the concomitant inhibition of the BRD4 and FGFR pathways might be a novel option for UM liver metastases. 203 …”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…The combination of the fibroblast growth factor receptor (FGFR) inhibitor AZD4547 with PLX51107 inhibited the growth of UM cells co-implanted with human stellate cells, indicating that the concomitant inhibition of the BRD4 and FGFR pathways might be a novel option for UM liver metastases. 203 …”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…25 It was reported that FGF-2 is a key contributor to bevacizumab resistance 26 and the drug resistance of chemotherapy in breast cancer and melanoma. [27][28][29] FGF-2 directly stimulates the survival and proliferation of tumor cells and indirectly facilitates tumor growth and metastasis by promoting the proliferation and migration of endothelial cells. 30 Many kinds of FGF-2 signaling inhibitors have been developed in preclinical studies or clinical trials, including nonspecific small-molecule tyrosine kinase inhibitors, such as dovitinib 31 and nintedanib, 32 as well as specific antagonistic large protein drugs, such as monoclonal antibodies 33 and soluble receptor fusion proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The present study by Chua et al () suggests that inhibition of the FGF receptor (FGFR) pathway improves the response of UMM to BET inhibitors. Specifically, they found that FGF2, but not other growth factors, provides resistance to growth suppression by BET inhibitors in UMM cells as well as in vivo .…”
mentioning
confidence: 56%
“…Intriguingly, different cancer types may share some of these deregulations, suggesting that very diverse cancers might display a common denominator for resistance development. As also described by Chua et al (), resistance to BET inhibitors in ovarian cancer was associated with elevated expression of FGFRs (Kurimchak et al , ). The mechanisms underlying BET inhibitor‐induced overexpression of FGFRs are unclear, but may involve modulation of BRD4‐induced regulation of FGFR transcription.…”
mentioning
confidence: 56%